A Scoping Review of Research on Comprehensive Primary Health Care (CPHC) in India - Neha Das; Charvi Mistry; Amol R Dongre (Online Journal of Health & Allied Sciences, 2023)
Background: The current situation of Comprehensive Primary Healthcare (CPHC) in India with reference to its characteristics is lesser known. Objectives: 1. To explore various characteristics of research based on CPHC in India. 2. To identify gaps in research on CPHC. Materials and Methods: A broad search strategy was developed to obtain articles on CPHC from PubMed and Google scholar. Out of 218 articles, 17 were explored for objectives, key findings. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for Scoping Reviews (PRISMA-ScR) was used. Results: Most were on reproductive and child health, non-communicable diseases, and utilization & gaps in services. Only one study was randomized controlled trial, followed by mixed method (n=2). Fourteen studies focussed on current situation of CPHC and none on service delivery of CPHC. Conclusion: Limited studies have been conducted on CPHC in India. Significant number of research are needed for strengthening primary health care.